Flexibility and Torsional Strength of ProTaper and ProTaper Universal Rotary Instruments Assessed by Mechanical Tests - Camara, Alexandre Sandri [UNESP]; Martins, Renata de Castro; Diniz Viana, Ana Cecilia; Leonardo, Renato de Toledo [UNESP]; Lopes Buono, Vicente Tadeu; de Azevedo Bahia, Maria Guiomar (Elsevier B.V., 2009)
The purpose of this study was to assess how the geometric and dimensional changes made on ProTaper Universal (PTU) instruments in comparison with ProTaper (PT) instruments affected their flexibility and torsional strength. Two groups (n = 12) of each type of shaping (S1 and S2) and finishing (F1, F2, and F3) for both PT and PTU instruments were employed. Tip angle, instrument diameter at each millimeter, and cross-sectional area at 3 mm from the tip were the dimensional parameters measured. Flexibility and torsional strength of each instrument (n = 12) were assessed according to specification ISO 3630-1. Data were analyzed using analysis of variance (alpha = 0.05). Flexibility increased for S1 and F1 PTU instruments and decreased for F2 and F3, whereas torsional resistance increased for S2, F2, and F3. Changes in tip angle were accompanied by variation of tip geometry in all instruments. (J Endod 2009;35:113-116)
Keywords: Flexibility; NiTi rotary instruments; ProTaper; ProTaper Universal; torsional resistance